Exploration and Antagonistic Test of Endophytic Fungi from Soybean (Glycine max L. Merr) With Different Resistance to Sclerotium rolfsii - Zuhria, Siti Aminatuz; Djauhari, Syamsuddin; Muhibuddin, Anton (Graduate School, Universitas Brawijaya, 2016)
The research aimed to determine the diversity of endophytic fungi in soybean crop with different resistance against Sclerotium rolfsii and find out their potential antagonist in controlling S.rolfsii by in vitro and in vivo. Materials used in this study were soybean with a variety of Wilis (susceptible variety) and Sinabung (resistant variety). This research was conducted at the Microbiology Laboratory of Central Laboratory of Life Science (LSIH), Brawijya University and in the trial plantation of Malang Research Institute for Food Crops, Lawang, Malang subdistrict in September 2015 until May 2016. Type of experimental design used was Complete Randomized Design with 16 treatments and three times repetitions at in vitro experiment with 16 treatments and four times repetitions at in vivo experiment. Observation on in vitro test is covering to colony morphology of fungal pathogens on PDA medium. On the test of in vivo, it was observed a disease occurrence and effectiveness rate of endophytic fungi. There are 15 species of endophytic fungi produced from isolation, namely Trichoderma sp., Aspergillus sp.2, Aspergillus sp.3, Acremonium sp.1, Acremonium sp.2, Acremonium sp.3, Acremonium sp.4, Fusarium sp.1, Fusarium sp.2, Cephalosporium sp, Microsporum sp., Penicillium sp., and unidentified fungi called W2 and W4. The highest inhibitory of endophytic fungi against S. rolfsii by Aspergillus sp.2 is 89.18% (in vitro) and 61.21% (in vivo), while Trichoderma sp. 91.88% (in vitro) and 63.29% (in vivo). Diversity index value of Wilis variety is higher than Sinabung, i.e. 1.878 and 1.606 respectively. While dominance index value of Sinabung variety is 0.2035 and Wilis is 0.1528. Keywords: Endophytic fungi, diversity, S. rolfsii.